Guiding Criteria and Ethical Codification: An Effective Model for Healthcare Professions (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The Italian regulatory framework has strengthened the role of codes of ethics for healthcare professions, giving them legal relevance in the evaluation of professional conduct. They guide ethical decisions, support the development of skills, and contribute to training. For ethical principles to translate into effectively applicable operational standards, their drafting must be inspired by certain guiding criteria. This article aims to provide a useful reference for those involved in the development and revision of codes of ethics, healthcare professionals, and students.
Keywords: codes of ethics; professional ethics; healthcare professions; professional responsibility; ethics education